Development of HAPAL Mobile Learning as a Science Learning Media for Junior High School Students - Purwanti, Purwanti; Hamdani, Nizar Alam; Rohayat, Asep; Darmawan, Deni; Rahadian, Dian; Hermana, Dody (Jurnal Paedagogy, 2025)
This research aims to develop HAPAL mobile learning products as a science learning media that is suitable for use by junior high school students. The research method used is research and development (R&D) with the ADDIE model. The research subjects used were media expert and material expert as well as class VIII students at SMPN 4 Pakenjeng Garut. The instrument used was a questionnaire for expert validation and student responses as users. The results of the media expert validation obtained an average value of 88.9 with a very valid category and the material expert obtained an average value of 86.39 with a very valid category. The average value of student responses to HAPAL mobile learning was 90.12 with a very valid category. So it can be concluded that HAPAL mobile learning is suitable for use in science learning at junior high school level.